Peningkatan Kemampuan Membaca Al-Quran Siswa Kelas IV Melalui Model Pembelajaran Poblem Based Learning di UPTD SDN 01 Labuah Gunuang - Alhusni Fuad; Erni Aftatika; Nurlela Nurlela; Roza Elfira; Fadhila Yusri; Adi Warman (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the low ability to read the Qur'an in grade IV students at UPTD SDN 01 Labuah Gunuang. This study aims to improve the ability to read the Qur'an of grade IV students at UPTD SDN 01 Labuah Gunuang through the talaqqi and tartil methods. The type of research used is Classroom Action Research (PTK) with the Problem Based Learning (PBL) model. The method used in the study is two cycles, namely the assignment methods. Each cycle consists of 4 stages, namely planning, implementation/action, observation/observation, and reflection. Each cycle consists of one meeting (3 lesson hours). The population used is 16 people. Data collection techniques used are observation, tests and interviews. The results of this study show an increase in students' ability to read the Qur'an from pre-action, cycle I and cycle II. The learning outcomes of students at the pre-action stage were 63,63%, in cycle I (first) increased to 81.82%, in cycle II (second) also increased to 18,19%. Thus, a recommendation can be submitted that the application of the assignment learning methods can improve students' ability to read the Qur'an on the material Reading the Qur'an Surah Al-Hujurat verse 13 for the 2024/2025 Academic Year.